Vitamin D Levels and Its Correlation with Severity of Breast Cancer - Anagha V. Sahasrabuddhe; Sanika Deshmukh; Shailesh U. Pitale; Chandrasekhar Mahakalkar; Ajonish Kamble (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Vitamin D has wide range of actions in the body which include immunogenic actions,differentiation of immune cells and keratinocytes, expression of growth factors etc. Genes encoding forproteins that regulate cellular differentiation, cell proliferation, apoptosis and angiogenesis contain vitaminD response element.Materials and Methods: A total of 135 newly diagnosed cases of breast cancer and equal number ofcontrols were recruited in the study. The histo-pathological grading of cancer, Hormone-receptor status(estrogen receptor-ER, progesterone receptor PR and HER-2 receptor) was done by immunohistochemistry,stage of tumor (based on TNM Classification), details of metastasis were noted. Vitamin D levels were doneby HPLC method.Results: The mean age, age at menarche, BMI, calcium intake, sun exposure, Ser PTH levels, Ser Calciumlevels were insignificantly different in both the groups. Ser Vitamin D levels were 30.95±17.65 ng/Ml incases and 27.21±7.97 ng/Ml in controls, with a p value of 0.198 which is not significant. The levels ofVitamin D in ng/Ml in Stage I, Stage II, Stage III and Stage IV were as follows: 26.06±11.45, 29.61±17.23,47.33±21.13, 42.67±28.92 and a p value of 0.190(NS). Thus there was no significant difference in VitaminD levels of cases and controls. The association between the biomarker status and stages showed significantresults as indicated by p-value of 0.043.Conclusion: This study fails to find any inverse association of vitamin D with severity of breast cancer andreceptor status.